2007
DOI: 10.1073/pnas.0704268104
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-like and crack-like ruptures in experiments mimicking crustal earthquakes

Abstract: Theoretical studies have shown that the issue of rupture modes has important implications for fault constitutive laws, stress conditions on faults, energy partition and heat generation during earthquakes, scaling laws, and spatiotemporal complexity of fault slip. Early theoretical models treated earthquakes as crack-like ruptures, but seismic inversions indicate that earthquake ruptures may propagate in a self-healing pulse-like mode. A number of explanations for the existence of slip pulses have been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
114
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(136 citation statements)
references
References 50 publications
21
114
0
1
Order By: Relevance
“…That is consistent with a range of calculations for different stress levels and forms of τ ss (V ); crack-like ruptures are not found, only self-healing slip pulses, when τ b 0 < τ pulse . The guidelines just outlined on when self-healing versus crack-like ruptures occur are also consistent with laboratory studies in which both types of ruptures were generated in different conditions (Lykotrafitis et al, 2006;Lu et al, 2007).…”
Section: Theoretical Background On Strong Rate-weakening and Self-heasupporting
confidence: 57%
“…That is consistent with a range of calculations for different stress levels and forms of τ ss (V ); crack-like ruptures are not found, only self-healing slip pulses, when τ b 0 < τ pulse . The guidelines just outlined on when self-healing versus crack-like ruptures occur are also consistent with laboratory studies in which both types of ruptures were generated in different conditions (Lykotrafitis et al, 2006;Lu et al, 2007).…”
Section: Theoretical Background On Strong Rate-weakening and Self-heasupporting
confidence: 57%
“…Lu et al (2007) have shown that this mechanism can be generalized and that the supershear transition can occur under various conditions such as when patches with lower static strength, high prestress, or a preexisting subcritical crack meet the P and S waves in front of the crack. Dunham et al (2003) proposed a barrier mechanism where rupture is first delayed by a high strength barrier, which then starts rupturing and leads to a supershear rupture due to stress concentration from the breaking of the barrier.…”
Section: Discussionmentioning
confidence: 99%
“…A rough fault is expected to favor pulselike ruptures with the rise time being only a small fraction of the total duration of the earthquake (Beroza and Mikumo, 1996;Nielsen et al, 2000). Recent experimental work (Lu et al, 2007) has shown that for smooth faults, both cracklike ruptures (where rise time is similar to total rupture duration) and self-healing pulses are possible depending on the prestress on the fault. Another outstanding and related issue concerns the influence of slip heterogeneity on the spectrum of the radiated seismic waves and near-source ground motion.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature interval through which a cooling pseudotachylyte may block a weak field TRM is at most a few hundreds of degrees and requires only a few seconds. Pulse-like seismic slip, such as that observed in experiments [Lu et al, 2007] could slightly expand this interval to tens of seconds.…”
Section: Origin(s) Of Nrm and Magnetization Mechanisms In Fault Pseudmentioning
confidence: 99%